Reclaiming Federal Spectrum: Proposals and Recommendations - Skorup, Brent (Science and Technology Law Review, 2013)
With the popularity of smartphones, tablets, Wi-Fi, and other wireless devices that require as an input transmissions over radio spectrum, the rising demand for bandwidth is rapidly using up the available supply of spectrum. Spectrum demand increases significantly every year with no end in sight, yet the “greenfields” of available and unallocated spectrum are gone. Redeployed spectrum must come from incumbent users. Today, the largest holder of spectrum appropriate for mobile broadband is the federal government, which uses spectrum for a variety of military and nonmilitary uses. Federal users generally use spectrum only lightly and the inefficiencies have triggered bipartisan calls for selling the spectrum used by federal agencies to the private sector, particularly to mobile broadband carriers. To date, reclaiming federal spectrum is a painfully slow process and billions of dollars of social welfare are lost with every year of delay. This Article examines proposals for reclaiming spectrum and puts forth some best practices to ensure more efficient use of spectrum. Policymakers should consider creating a commission with authority to require the sale of spectrum so that agency-controlled spectrum is quickly and easily redeployed to its highest-valued uses. In the long run, Congress should also require agencies to pay for the spectrum they possess, just as agencies pay market prices for other inputs.